Rethinking Islamization in Southeast Asia: Historical Dynamics, Distinction and Existence of Muslim - Fadhil, Haidar Masyhur; Imtyas, Rizkiyatul (Journal of Modern Islamic Studies and Civilization, 2024)
This article discusses the process of Islamization in Southeast Asia, theories based on historical evidence, and so on. Then how the characteristics of Islam in Southeast Asia, which of course, in terms of geography, culture, and the process of Islamization is, different from Islamization in other regions. The paper explains that Islamization in Southeast Asia was peaceful and wasatiyya brought by the preachers, Sufi, and Muslim merchants who traded in the strategic Southeast Asian region. Islam in Southeast Asia, especially in Indonesia, is an Islam that is attached to local culture and is slightly arabized so that the natives can well accept it at that time. Although many western scholars argue that Islam in Southeast Asia is peripheral Islam because of its characteristics that are not like pure Islam in the Middle East, their arguments are not based on concrete evidence, so they need to be questioned more deeply. Therefore, the paper will discuss Islam in Southeast Asia, including its history, characteristics, and distinctions, and how western scholars perceive Southeast Asian Islam as peripheral.